2020
DOI: 10.3390/ma13184155
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Third Element on Nano-Mechanical Properties of Iron Borides FeB and Fe2B Formed in Fe-B-X (X = C, Cr, Mn, V, W, Mn + V) Alloys

Abstract: In this study, the influence of alloying elements on the mechanical properties of iron borides FeB and Fe2B formed in Fe-B-X (X = C, Cr, Mn, V, W, Mn + V) alloys were evaluated using instrumented indentation measurement. The microstructural characterization of the alloys was performed by means of X-ray diffraction and scanning electron microscope equipped with an energy dispersive X-ray analyzer. The fraction of the phases present in the alloys was determined either by the lever rule or by image analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The latter is explained by inherent brittleness of Fe 2 B due to the week B–B bond along [002] direction [ 77 , 78 ], which leads to a great susceptibility of boron alloys to cracking. Kirkovska et al [ 79 ] showed that among the alloying elements C, Cr, Mn, V, W, Mn + V, the greatest increase in the indentation modulus of both monoboride FeВ and hemioboride Fe 2 B, was observed in alloying with chromium. Whereas the lowest modulus in the case of FeB formed in Fe–B–X (X = C, Cr, Mn) was measured in the presence of C as an alloying element, while for Fe 2 B, in Mn alloyed Fe 2 B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is explained by inherent brittleness of Fe 2 B due to the week B–B bond along [002] direction [ 77 , 78 ], which leads to a great susceptibility of boron alloys to cracking. Kirkovska et al [ 79 ] showed that among the alloying elements C, Cr, Mn, V, W, Mn + V, the greatest increase in the indentation modulus of both monoboride FeВ and hemioboride Fe 2 B, was observed in alloying with chromium. Whereas the lowest modulus in the case of FeB formed in Fe–B–X (X = C, Cr, Mn) was measured in the presence of C as an alloying element, while for Fe 2 B, in Mn alloyed Fe 2 B.…”
Section: Introductionmentioning
confidence: 99%
“…At that, Fe 2 B with a tetragonal lattice is less brittle. Further improvement of the mechanical properties of hemioboride due to additional alloying of the boride [ 67 , 79 ] elements (Ti, V, Cr, Co, Ni, and Cu) showed that it can enhance the ductility of the Fe 2 B, but cannot change the intrinsic brittle nature of the Fe 2 B [ 67 ]. Copper increases the plastic properties of hemioboride most of all the range of alloying elements M = Ti, V, Cr, Mn, Co, Ni and Cu (Fe 0.875 M 0.125 ) 2 B, at the same time, the value of G/B (0.5883) is close to the critical value of the ductile/brittleness transition (0.571) [ 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metallic glasses have unique combinations of mechanical properties, corrosion resistance and magnetic property due to their non-crystalline structure. In recent years, more and more studies have focused on metallic glass, such as amorphous nanocrystalline powder, amorphous strips and so on [12][13][14][15][16]. A kind of amorphous Fe-W-B nano-powder was obtained via a chemical method [17]; nevertheless, the low yield makes it difficult to realize mass production.…”
Section: Introductionmentioning
confidence: 99%